The Round Tower of Abernethy: with drawings - Brash, Richard Rolt (Proceedings of the Society of Antiquaries of Scotland, 1862)
The article presents the history of Abernethy as a royal and religious site before moving on to the writings of some antiquarians who previously studied the tower referenced in the title. The author discusses his own observations and measurements of the tower and compares this round tower to other Scottish and Irish examples. He argues that this tower was partially rebuilt in the 11th or 12th century. The article concludes with information on other partially rebuilt towers and some of the legends surrounding this kind of structure.